“You made us think”: The path-breakers battling land degradation in Samoa’s rural communities - Leaupepe, Aloema (Technical Centre for Agricultural and Rural Cooperation, 2018)
A training programme covering the basics of permaculture and of a healthy lifestyle is promoting sustainable development and enabling communities across Samoa to combat the adverse effects of climate change. Drawing upon Samoan heritage, the Taiala programme placed an emphasis upon community-led education and communal learning in farmer’s cooperative societies. Through the guidance of Matuaileoo Environment Trust Inc.’s Taiala programme, 10 villages have now adopted a more ecologically attuned world-view.